Modern Productivity Management: Why Work Systems Fail to Produce High Performance - Jonner Simarmata; Evi Adriani (Greenation Research & Yayasan Global Resarch National, 2026)
The development of digital technology and modern work systems is often assumed to increase organizational productivity and performance. However, in practice, many organizations experience increased workloads without corresponding improvements in performance quality. This article aims to analyze why modern work systems often fail to produce high performance, despite being supported by increasingly sophisticated management practices and technology. Using a narrative-critical literature review approach to scientific publications in the fields of management, cognitive psychology, and organizational behavior from 2015 to 2025, this article examines the relationship between work system design, cognitive limitations, planning biases, emotional regulation, and performance sustainability. The analysis shows that modern work systems are built on assumptions that are at odds with human cognitive and emotional capacities, such as demands for multitasking, constant responsiveness, and overly optimistic performance targets. These conditions foster the illusion of activity-based productivity, increase cognitive load and emotional stress, and hinder deep focus and quality decision-making. This article contributes to the productivity management literature by asserting that productivity is a systemic phenomenon that depends on the alignment between work system design and human psychological capacities. The article's practical implications emphasize the importance of shifting work systems toward sustainable, high-quality performance.